Managing Services - Nankervis, Alan (Cambridge University Press, 2005)
Global services have supplanted agriculture, manufacturing and resources, as the primary source of international competitive advantage in many countries, providing wealth, employment, and almost unlimited future opportunities for growth, whether in traditional or more innovative forms. This book explores the strategic management of services through an Integrated Services Management Model which links operational, marketing, financial and human resource management functions, within a broad and diverse collection of international, regional, and local service contexts. It contains numerous case examples, student projects and exercises, with a particular focus on the Asia Pacific and Australasian regions.